2009
DOI: 10.1016/j.bbcan.2009.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional control of the tumor- and hypoxia-marker carbonic anhydrase 9: A one transcription factor (HIF-1) show?

Abstract: SUMMARYTranscriptional activation by hypoxia is mediated by the hypoxia-inducible factor (HIF) via binding to the hypoxia-responsive element (HRE). Hypoxia in solid tumors associates with poorer outcome of the disease and reliable cellular markers of tumor hypoxia would represent a valuable diagnostic marker and a potential therapeutic target. In this category, carbonic anhydrase IX (CAIX) is one of the most promising candidates. Here, we summarize the knowledge about transcriptional regulation of CA9. The HRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
216
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(223 citation statements)
references
References 72 publications
7
216
0
Order By: Relevance
“…A number of genes involved in cell growth, cell shape, cell movement, cell fate, and cell communication are regulated by AP-2 family (19)(20)(21)(22). Reduced, or overexpressed TFAP2A expression is often detected in several types of cancers, such as melanoma, prostate, breast, ovary, neuroglioma, gastric, colon, and bladder cancers (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), indicating that loss of TFAP2A function, or TFAP2A overexpression may contribute to tumorigenesis and development of tumor malignancy. However, the biological role, prognostic value, and clinical significance of TFAP2, as well as its mechanism of action in nasopharyngeal carcinoma growth and progression remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A number of genes involved in cell growth, cell shape, cell movement, cell fate, and cell communication are regulated by AP-2 family (19)(20)(21)(22). Reduced, or overexpressed TFAP2A expression is often detected in several types of cancers, such as melanoma, prostate, breast, ovary, neuroglioma, gastric, colon, and bladder cancers (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), indicating that loss of TFAP2A function, or TFAP2A overexpression may contribute to tumorigenesis and development of tumor malignancy. However, the biological role, prognostic value, and clinical significance of TFAP2, as well as its mechanism of action in nasopharyngeal carcinoma growth and progression remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…GLUT-1 is involved in the metabolic adaptation of the cell to hypoxia by increasing the intracellular glucose supply, which might be regulated by HIF-1α (Rademakers et al, 2011). CA-9, one of the 15 carbonic anhydrase isoforms in humans, which is exclusively transactivated by HIF-1α, has recently emerged as one of the most promising endogenous hypoxia-related markers of cellular hypoxia (Kaluz et al, 2009). Angiogenesis is an essential biological process not only in embryogenesis but also in the progression of a variety of major diseases such as cancer, diabetes and inflammation (Shibuya, 2001).…”
mentioning
confidence: 99%
“…The increasing HIF level along with hypoxia in the tumor microenvironment also triggers the expression of CA-9. It has been reported that the level of CA-9 was high and closely associated with adverse survival in many solid tumors such as cervix, kidney, stomach, lung, and head and neck cancers (50). In a study conducted in head and neck cancer cell lines and tumor specimens, it was found that CA-9 was expressed at an increased rate and was higher in advanced stage tumors (51).…”
Section: Hypoxia In the Tumor Microenvironmentmentioning
confidence: 99%